Digestibilidade de alimentos energéticos suplementados com fitase para o jundiá (Rhamdia voulezi) - Lewandowski, Vanessa (2015)
The aim of the study was to evaluate the digestibility of oat, rice grits, and wheat middling nutrients by silver catfish (Rhamdia voulezi), with and without phytase supplementation. We used 288 fish distributed in 24 tanks of 500 L with tapered conical bottom. The experimental design was completely randomized represented by eight treatments and three replications. The treatments consisted of two reference diets (reference with and without phytase) and six test diets (oats with and without phytase, rice grits with and without phytase and wheat middling with and without phytase), factorial design, obtaining four diets without enzyme supplementation and four diets with supplementation. In the supplemented diets we added 1500 FTU kg-1 of phytase. We performed chemical, physical and mineral (phosphorus, calcium, magnesium, iron and cupper) analysis of the ingredients, diets and feces, as well as chromium oxide measurement of the diets and feces. The digestibility coefficients observed were submitted to factorial variance analysis (P>0,05). When a significant effect was observed, the Tukey s test was performed for mean comparisons. Oat presented the lowest digestibility coefficients for dry matter and energy compared to the other feeds supplemented or not with phytase. Phytase supplementation increased the digestibility coefficient of dry matter for rice grits, and of energy both for this feed and for wheat middling. As for the use of minerals we verified that wheat middling presented the highest digestibility coefficients related to feed without phytase as much as for feed supplemented with the enzyme. The supplementation of phytase in quantity of 1500 FTU kg-1 in the diet improves the nutrients digestibility coefficients mainly for oat and rice grits. Taking into account the feeds with or without supplementation of 1500 FTU kg-1 in the diet, rice grits and wheat middling presented the highest values of its nutrients use and can be used more efficiently for silver catfish (R. voulezi) feeding.